2019
DOI: 10.1371/journal.pone.0223952
|View full text |Cite
|
Sign up to set email alerts
|

The respiratory virome and exacerbations in patients with chronic obstructive pulmonary disease

Abstract: IntroductionExacerbations are major contributors to morbidity and mortality in patients with chronic obstructive pulmonary disease (COPD), and respiratory bacterial and viral infections are an important trigger. However, using conventional diagnostic techniques, a causative agent is not always found. Metagenomic next-generation sequencing (mNGS) allows analysis of the complete virome, but has not yet been applied in COPD exacerbations.ObjectivesTo study the respiratory virome in nasopharyngeal samples during C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 46 publications
(54 reference statements)
0
44
1
Order By: Relevance
“…Results presented in pharyngeal clinical samples showed that the greatest amounts of viral sequences from mammalian viruses were present in the families Coronaviridae, Anelloviridae, and Paramyxoviridae, Coronaviridae and Anelloviridae comprising the major part of the composition. Both Coronaviridae and Anelloviridae were detected in the same sample in the present research ( Figure 4B), which was inconsistent with previous studies where Anelloviridae were not detected in the Coronaviridaepositive samples and Coronaviridae were not detected in the Anelloviridae-positive samples (van Rijn et al, 2019). We also observed that the M3 did not detecte Herpesviridae, which were thought to have possibly integrated into the human genome.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Results presented in pharyngeal clinical samples showed that the greatest amounts of viral sequences from mammalian viruses were present in the families Coronaviridae, Anelloviridae, and Paramyxoviridae, Coronaviridae and Anelloviridae comprising the major part of the composition. Both Coronaviridae and Anelloviridae were detected in the same sample in the present research ( Figure 4B), which was inconsistent with previous studies where Anelloviridae were not detected in the Coronaviridaepositive samples and Coronaviridae were not detected in the Anelloviridae-positive samples (van Rijn et al, 2019). We also observed that the M3 did not detecte Herpesviridae, which were thought to have possibly integrated into the human genome.…”
Section: Discussioncontrasting
confidence: 99%
“…Common human respiratory tract viruses have been summarized for the period from 2009 to 2016, including Rhinoviruses, Paramyxoviruses, Orthomyxoviruses, Coronaviruses, Adenoviruses, Parvoviruses, Herpesviruses, Anelloviruses, Papillomaviruses, and Polyomaviruses (Wylie, 2017). To date, only one study characterized respiratory virome in the areas of COPD in 63 patients with acute COPD exacerbation from Norway, in which an obtained median of 11 million sequence reads per sample contained ∼93% of human reads, 3% of bacterial, 0.1% of viral, and 3% of unknown reads, as identified using NGS without any viral enrichment steps (van Rijn et al, 2019). In this study, we aimed to optimize the pretreatment method to enrich viral particles for NGS sequencing to investigate the virome in pharyngeal clinical samples from hospitalized patients with acute COPD exacerbation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For quantification of viral reads 8,14,17 , reads were normalized according to the number of preprocessed reads (adaptor-trimmed reads with exclusion of low-quality and low-complexity sequences) and expressed in reads per million (RPM). RPM values corresponding to presumptive viral laboratory, reagent, and/or cross-contaminants in the negative control samples were subtracted from clinical stool samples in the same sequencing batch, with negative RPM values after subtraction set to 0.…”
Section: Nucleic Acid Extractionmentioning
confidence: 99%
“…The development of chronic airway inflammatory diseases is usually linked to specific bacterial species in the microbiome which may thrive in the inflamed airway environment (Diver et al, 2019). In the event of a viral infection such as RV infection, the effect induced by the virus may destabilize the equilibrium of the microbiome present (Molyneaux et al, 2013;Kloepfer et al, 2014;Kloepfer et al, 2017;Jubinville et al, 2018;van Rijn et al, 2019). In addition, viral infection may disrupt biofilm colonies in the upper airway (e.g., Streptococcus pneumoniae) microbiome to be release into the lower airway and worsening the inflammation (Marks et al, 2013;Chao et al, 2014).…”
Section: Alteration Of Airway Microbiomementioning
confidence: 99%